Helping couples and families navigate illness and disability : an integrated approach - Rolland, John S., 1948- (The Guilford Press, 2018)
"Couples and families face daunting challenges as they cope with serious illness and disability. This book gives clinicians a roadmap for helping affected individuals and their loved ones live well with a wide range of child, adult, and later-life conditions. John S. Rolland describes ways to intervene with emerging challenges over the course of long-term or life-threatening disorders. Using vivid case examples, he illustrates how clinicians can help families harness their strengths for positive adaptation and relational growth. Rolland's integrated systemic approach is useful for preventive screening, consultations, brief counseling, more intensive therapy, and multifamily groups, across health care settings and disciplines. This book significantly advances the clinical utility of Rolland's earlier landmark volume, Families, Illness, and Disability. Key Words/Subject Areas: medical family therapy, coup therapy, couples therapy, marriage, marital problems, chronic illness, terminal illness, medical conditions, health problems, dementia, disease, disability, developmental disabilities, physical disabilitiesle, integrated care, integrative care, death and dying, children, adults, families, parents, caregiving, caregivers, interventions, treatments, techniques, Family Systems Illness model, hospice care, healthcare system Audience: Couple and family therapists and counselors, clinical psychologists, social workers, pastoral counselors, nurses, and psychiatrists"--